Electrocardiographic signs of the left main coronary artery disease in acute coronary syndrome - E. S. Eniseeva; K. V. Protasov; G. P. Gurtovaya (Российский кардиологический журнал, 2020)
Myocardial infarction (MI) due to the left main coronary artery (LMCA) disease is a life-threatening condition. Evaluation of ECG signs of LMCA occlusion is important because of revascularization emergency. There is no single ECG pattern for LMCA occlusion. The purpose of the present literature review is to reveal ECG potential in diagnosing LMCA occlusion in acute coronary syndrome. Variability of ECG abnormalities was noted depending on the degree of LMCA occlusion, collateral blood flow from the right coronary artery, and concomitant stenosis. ST elevation in aVR is an evident predictor of LMCA lesion. Electrophysiological mechanisms of its formation were described. Diagnostic significance of additional ECG signs of LMCA disease was presented. Diagnostic and treatment strategies for patients with ECG signs of severe LMCA disease were summarized.